Hospital food: When nurses' and ethnic minority patients' understanding of Islamic dietary needs differ - Lise‐Merete Alpers (Wiley, 2019)
Abstract Aim The aim of this study was to investigate how medical unit nurses assess their knowledge about Muslim patients' dietary preferences and needs and Muslim patients' needs regarding food. Design Mixed‐method design. Methods Two‐part study. Part 1: Two focus group interviews and a survey answered by medical unit nurses. Part 2: In‐depth interviews with ten immigrant patients (eight Asians and two Africans). Hermeneutic analysis of qualitative data and SPSS were used for descriptive analysis of the quantitative data. Results The nurses' knowledge about acceptable and prohibited food within Islam appears to be simplistic and Muslim patients tended to be perceived as a homogenous group. Patients' distrust about the preparation and content of the food served may result in insufficient nutritional intake. Serving food that is acceptable to individual patients requires insight and is an essential part of culturally sensitive nursing care.